Structural Refinement, Recrystallization and Grain Growth Phenomena in an Accumulative Roll Bonded Nickel Sheet - Quadir, Md Zakaria; Duan, J.; Xu, W.; Ferry, M. (2017)
© 2017 The Authors. The thickness of the lamellar band (LB) structure that is generated in an accumulative roll bonded nickel sheet represents the degree of structure refinement. The LBs reach a saturation in thickness after several roll bonding cycles due to adiabatic heating that balances the dislocations generated during rolling. The thermal restoration process starts with the rearrangement of dislocations and boundary migration. At the initial stages of thermal restoration, LBs with all the orientations in the deformation texture grow by the so-called continuous recrystallization process. However, in the latter stages, growth becomes orientation selective and dominated by S and copper orientations. Finally, grain growth after recrystallization results in the preferred growth of Cube-oriented grains to the full layer thickness of the ARB sheet, thereby generating a strong Cube texture. Thus, grain growth yields a final texture similar to that generated in conventionally rolled and annealed nickel sheets.